Natural Language Processing and Chinese Computing 12th National CCF Conference, NLPCC 2023, Foshan, China, October 12-15, 2023, Proceedings, Part I - Liu, Fei.; Duan, Nan.; Xu, Qingting; Hong, Yu. (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This three-volume set constitutes the refereed proceedings of the 12th National CCF Conference on Natural Language Processing and Chinese Computing, NLPCC 2023, held in Foshan, China, during October 12-15, 2023. The 143 regular papers included in these proceedings were carefully reviewed and selected from 478 submissions. They were organized in topical sections as follows: dialogue systems; fundamentals of NLP; information extraction and knowledge graph; machine learning for NLP; machine translation and multilinguality; multimodality and explainability; NLP applications and text mining; question answering; large language models; summarization and generation; student workshop; and evaluation workshop.
Dialogue Systems -- A Task-oriented Dialog Model with Task-progressive and Policy-aware Pre-training -- Retrieval-Augmented Knowledge-Intensive Dialogue -- Episode-based Prompt Learning for Any-shot Intent Detection -- CrossDial: An Entertaining Dialogue Dataset of Chinese Crosstalk -- Fundamentals of NLP -- Recurrent Transformers for Long Document Understanding -- SCA-CLS: A New Semantic-Context-Aware Framework for Community-Oriented Lexical Simplification -- A Cross-lingual Sentiment Embedding Model with Semantic and Sentiment Joint Learning -- Learning to Attentively Represent Distinctive Information for Semantic Text Matching -- Information Extraction and Knowledge Graph -- Reasoning Through Memorization: Nearest Neighbor Knowledge Graph Embeddings -- MACO: A Modality Adversarial and Contrastive Framework for Modality-missing Multi-modal Knowledge Graph Completion -- A Joint Entity and Relation Extraction Approach Using Dilated Convolution and Context Fusion -- Interest Aware Dual-channel Graph Contrastive Learning for Session-based Recommendation -- Chinese Event Causality Identification Based on Retrieval Enhancement -- UZNER: A Benchmark for Named Entity Recognition in Uzbek -- Evaluation Framework for Poisoning Attacks on Knowledge Graph Embeddings -- Label-guided Compressed Prototypical Network for Incremental Few-shot Text Classification -- Auxiliary Information Enhanced Span-based Model for Nested Named Entity Recognition -- DialogRE$^{C+}$: An Extension of DialogRE to Investigate How Much Coreference Helps Relation Extraction in Dialogs -- A Bi-directional Multi-hop Inference Model for Joint Dialog Sentiment Classification and Act Recognition -- Positive-guided Knowledge Distillation for Document-level Relation Extraction with Noisy Labeled Data -- PromptCL: Improving Event Representation via Prompt Template and Contrastive Learning -- RMGCN: Masked Graph Convolutional Networks for Relation-Aware Entity Alignment with Dangling Cases -- SymCoNLL: A Symmetry-based Approach for Document Coreference Resolution -- What Makes a Charge? Identifying Charge-Discriminative Facts with Legal Elements -- Machine Learning for NLP -- A New Encoder Using Character and Word Feature Fusion for Chinese Math Word Problem Solving -- MarkBERT: Marking Word Boundaries Improves Chinese BERT -- MCVIE: An Effective Batch-Mode Active Learning for Multi-Label Text Classification -- Task-consistent Meta Learning for Low-resource Speech Recognition -- An Adaptive Learning Method for Solving the Extreme Learning Rate Problem of Transformer -- Machine Translation and Multilinguality -- Towards Making the Most of LLM for Translation Quality Estimation -- Towards Better Translations from Classical to Modern Chinese: A New Dataset and a New Method -- Imitation Attacks Can Steal More than You Think from Machine Translation Systems -- Monolingual Denoising with Large Language Models for Low-Resource Machine Translation -- Multimodality and Explainability -- CAMG: Context-Aware Moment Graph Network for Multimodal Temporal Activity Localization via Language -- Semantic Extension for Cross-Modal Retrieval of Medical Image-Diagnosis Report -- ECOD: A Multi-Modal Dataset for Intelligent Adjudication of E-Commerce Order Disputes -- Bounding and Filling: A Fast and Flexible Framework for Image Captioning -- NLP Applications and Text Mining -- ASKSpell: Adaptive Surface Knowledge Enhances Tokens' Semantic Representations for Chinese Spelling Check -- Biomedical Entity Normalization Using Encoder Regularization and Dynamic Ranking Mechanism -- Legal Judgment Prediction Incorporating Guiding Cases Matching -- Punctuation Matters! Stealthy Backdoor Attack for Language Models -- SeSQL: A High-quality Large-scale Session-level Chinese Text-to-SQL Dataset -- RSpell: Retrieval-augmented Framework for Domain Adaptive Chinese Spelling Check -- Exploiting Multiple Features for Hash Codes Learning with Semantic-Alignment-Promoting Variational Auto-encoder -- Enhancing Detailed Feedback to Chinese Writing Learners Using a Soft-Label Driven Approach and Tag-Aware Ranking Model -- Question Answering -- NAPG: Non-Autoregressive Program Generation for Hybrid Tabular-Textual Question Answering -- Mixture-of-Experts for Biomedical Question Answering -- Fine-grained Question-Answer Matching via Sentence-aware Contrastive Self-supervised Transfer -- KARN:Knowledge Augmented Reasoning Network for Question Answering -- Large Language Models -- Creative Destruction: Can Language Models Interpret Oxymorons? -- Global Prompt Cell: A Portable Control Module for Effective Prompt Tuning -- What Events Do Pre-trained Language Models Learn from Text? Probing Event-based Commonsense Knowledge by Confidence Sorting -- Revisit Input Perturbation Problems for LLMs: A Unified Robustness Evaluation Framework for Noisy Slot Filling Task -- Large Language Models are Diverse Role-Players for Summarization Evaluation -- COSYWA: Enhancing Semantic Integrity in Watermarking Natural Language Generation -- Summarization and Generation -- Multi-Step Review Generation Based on Masked Language Model for Cross-Domain Aspect-Based Sentiment Analysis -- rT5: A Retrieval-Augmented Pre-Trained Model for Ancient Chinese Entity Description Generation -- Probing Bilingual Guidance for Cross-Lingual Summarization -- Accurate, Diverse and Multiple Distractor Generation with Mixture of Experts -- Improve the Diversity and Novelty for Open-ended Neural Text Generation via Inverse Probability Weighting -- Dialogue Systems -- A Unified Generation Approach for Robust Dialogue State Tracking -- An Explicit-Memory Few-shot Joint Learning Model -- A Noise-Removal of Knowledge Graph Framework for Profile-based Spoken Language Understanding -- Bilevel Scheduled Sampling for Dialogue Generation -- Dial-QP: A Multi-Tasking and Keyword-Guided Approach for Enhancing Conversational Query Production -- Discourse Relation-Aware Multi-turn Dialogue Response Generation.
Keywords: Artificial intelligence; Artificial Intelligence